2016
DOI: 10.1002/wps.20348
|View full text |Cite
|
Sign up to set email alerts
|

“Prolonged grief disorder” and “persistent complex bereavement disorder”, but not “complicated grief”, are one and the same diagnostic entity: an analysis of data from the Yale Bereavement Study

Abstract: There exists a general consensus that prolonged grief disorder (PGD), or some variant of PGD, represents a distinct mental disorder worthy of diagnosis and treatment. Nevertheless, confusion remains over whether different names and proposed symptom criteria for this disorder identify the same or different diagnostic entities. This study aimed to determine whether PGD, complicated grief (CG), and persistent complex bereavement disorder (PCBD) as described by the DSM-5 are substantively or merely semantically di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
238
0
12

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 260 publications
(265 citation statements)
references
References 37 publications
15
238
0
12
Order By: Relevance
“…In a 2016 study, the new PGD ICD-11 symptom criteria (of note, this was a shortened item list of two core symptoms and five symptoms of emotional pain) were compared to the PGD-2009 criteria, the PCBD criteria of the DSM-5 and CG through a reanalysis of the Yale Bereavement Study data (Maciejewski et al, 2016). This was a longitudinal interview based study of a sample of 317 bereaved individuals.…”
Section: Evidence For the Clinically Useful Symptom Structure Of Icd-mentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2016 study, the new PGD ICD-11 symptom criteria (of note, this was a shortened item list of two core symptoms and five symptoms of emotional pain) were compared to the PGD-2009 criteria, the PCBD criteria of the DSM-5 and CG through a reanalysis of the Yale Bereavement Study data (Maciejewski et al, 2016). This was a longitudinal interview based study of a sample of 317 bereaved individuals.…”
Section: Evidence For the Clinically Useful Symptom Structure Of Icd-mentioning
confidence: 99%
“…The PGD-2009 criteria and CG criteria differ in terms of the populations in which they were assessed, the statistical methods used to assess the criteria, the number of items required to receive a diagnosis and descriptions of the items (Maciejewski & Prigerson, 2017; Reynolds et al, 2017). It should be noted that at the time of the revision of the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition (DSM-IV), persistent complex bereavement disorder (PCBD) was introduced as a compromise between the two proposed diagnostic criteria for PGD and CG and placed in section III of the 5th Edition of DSM (DSM-5) as a disorder requiring further study (Maciejewski, Maercker, Boelen, & Prigerson, 2016; Reynolds et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…PGD has been differentiated from Post-Traumatic Stress Disorder (PTSD) and post-loss depression (Boelen & Van Den Bout, 2005; Bonanno et al, 2007; Lichtenthal, Cruess, & Prigerson, 2004). It is referred to as Persistent Complex Bereavement Disorder under the section on conditions for further study in the DSM-5 (American Psychological Association, 2013), and will be introduced as a mental health diagnosis in the ICD-11 (World Health Organization, 2018; Maciejewski, Maercker, Boelen, & Prigerson, 2016). PGD also predicts a host of additional health problems, including heart disease, high blood pressure, cancer (Prigerson et al, 1997; Prigerson, Vanderwerker, & Maciejewski, 2008), suicidality (Latham & Prigerson, 2004), substance abuse, depression, anxiety, and overall life disruption (Boelen & Prigerson, 2007; Ott, 2003; Shear et al, 2011).…”
mentioning
confidence: 99%
“…There have been attempts to distinguish between normal grief and a collection of symptoms that would warrant a diagnostic label. The most current labels are Persistent Complex Bereavement Disorder (PCBD) as defined in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (American Psychiatric Association, 2013) and Prolonged Grief Disorder (PGD) which has been proposed for inclusion in the 11th revision of the International Classification of Diseases (ICD-11; Maciejewski, Maercker, Boelen, & Prigerson, 2016). These diagnostic classifications are met when the grief reaction is prolonged and accompanied by symptoms such as yearning for the deceased, preoccupation with the deceased or their death, and difficulty accepting the loss.…”
mentioning
confidence: 99%
“…These diagnostic classifications are met when the grief reaction is prolonged and accompanied by symptoms such as yearning for the deceased, preoccupation with the deceased or their death, and difficulty accepting the loss. Maciejewski et al (2016) suggested that there are no substantive differences between PGD and PCBD and that each is associated with a prevalence rate of around 10%. Issues surrounding the controversy over a proposed diagnostic criteria for grief (either PGD or PCBD) are the potential for pathologizing what may be considered normal reactions to loss.…”
mentioning
confidence: 99%